EVALUATING THE ECOPHYSIOLOGY OF SURVIVAL FOR MAPANIA CUSPIDATA (MIQ.) UITTIEN (CYPERACEAE) TRANSPLANTATION - Zinnirah Shabdin; Hollena Nori; Kalu Meekiong; Mohammad Fajaruddin Mohd Faiz (REINWARDTIA, 2021)
SHABDIN, Z., NORI, H., MEEKIONG, K. & FAIZ, M. F. M. 2021. Evaluating the ecophysiology of survival for Mapania cuspidata (Miq.) Uittien (Cyperaceae) transplantation. Reinwardtia 20(2): 69–75. — This study aimed to investigate the ecology of the sedge Mapania cuspidata at three different locations in East Malaysia, namely Gunung Gading, Matang and Bengoh, and the survival of M. cuspidata transplanted in pots exposed to different light intensities in Universiti Malaysia Sarawak, East Malaysia. The highest species density was recorded in Matang with a total density of 1.98 individuals/ha followed by Bengoh (1.42) and Gunung Gading (0.96). In these locations, the soil pH ranged from 4.9 in Bengoh to 5.7 in Matang where as soil organic matter content was between 3.47% in Bengoh and 8.68% in Gunung Gading. The highest light intensity was recorded in Matang with 0.94 kLux, and produced plants with the highest chorophyll content (64.8 SPAD value). This study found that the transplanted M. cuspidata had 90% survival over a four month experiment, produced ~ 8 new leaves, took an average of 15.8 days to produce a new leaf and had a chlorophyll content of ~30.3 SPAD value regardless of the intensity of light where the plants were exposed to. The findings of this study suggests that M. cuspidata can grow well in any light conditions and therefore it is also possible to transplant and re-establish other Mapania species in new location. It is hoped that the initiative to relocateother Mapania species of concervation concern will be effective if adequate post-harvest handling methods are practiced.